Factores de riesgo y su incidencia en la lumbalgia en pacientes mayores de 40 años que acuden a rehabilitación al Hospital Nicolás Cotto Infante, Vinces – los ríos. Junio - octubre 2023. - Fuentes Cedeño, Edison Fernando (2023)
Low back pain continues to top the list of the most common musculoskeletal disorders with the highest incidence in the adult population. At the Nicolás Cotto Infante - Vinces hospital, only in the month of July there were a total of 15 new cases that came to rehabilitation, compared to the month of January in which the figure was a total of 8 patients. For this reason, the main basis of our study consisted in determining the factors associated with low back pain in patients over 40 years of age who attend rehabilitation at the Nicolás Cotto Infante Hospital during the period of January-July 2023, finding that factors that are related between each patient such as the type of work activity, body mass index (BMI), age, lack of physical activity, etc. In order to determine these factors, a deductive bibliographic research with qualitative-quantitative techniques was chosen to obtain the necessary data to carry out our research. There was a population of 84 patients and we worked with a total sample of 64. We use instruments such as interviews, where we had contact with the study population, in addition to carrying out a survey in order to define age, height and weight, type of work activity and, above all, the intensity of pain perceived by each patient. Based on that, the percentages that stood out the most were that 63% of the study population was female, 44% had an age range of between 40 to 50 years, 56% were overweight, 37 % performed less than 30 minutes of scheduled physical activity per week, 35% worked within the agricultural area, 83% stated that their work activity influenced their low back pain and 48% identified a mild intensity of pain on the Visual Analogue Scale (VAS).